2008
DOI: 10.1016/j.specom.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Supervised and unsupervised learning of multidimensionally varying non-native speech categories

Abstract: Learning to recognize the contrasts of a language-specific phonemic repertoire can be viewed as forming categories in a multidimensional psychophysical space. Research on the learning of distributionally defined visual categories has shown that categories defined over 1 dimension are easy to learn and that learning multidimensional categories is more difficult but tractable under specific task conditions. In 2 experiments, adult participants learned either a unidimensional or a multidimensional category distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 56 publications
6
98
2
Order By: Relevance
“…Vowel production data analyzed in Neri et al (2006) are in line with the vowel perception data reported on in Goudbeek et al (2008) in suggesting that distinctions based on two dimensions are problematic for DL2 learners. For example, in Neri et al (2006), DL2 learners with different language background appeared to confuse /A/ with /a+/, /I/ with /i/ and /O/ with /o+/.…”
Section: A Case In Point: the Dutch Vowel Systemsupporting
confidence: 78%
See 3 more Smart Citations
“…Vowel production data analyzed in Neri et al (2006) are in line with the vowel perception data reported on in Goudbeek et al (2008) in suggesting that distinctions based on two dimensions are problematic for DL2 learners. For example, in Neri et al (2006), DL2 learners with different language background appeared to confuse /A/ with /a+/, /I/ with /i/ and /O/ with /o+/.…”
Section: A Case In Point: the Dutch Vowel Systemsupporting
confidence: 78%
“…The difficulties experienced by DL2 learners in perceiving Dutch vowels appear to be connected to the relation between the Dutch vowel system and that of their L1 and in particular to how L2 vowels map on to vowels in the native phonology (Escudero and Boersma, 2004;Goudbeek et al, 2008). In general, distinctions based on dimensions that are not relevant in the L1 are likely to be more difficult than distinctions that hinge on cues that are exploited in the native phonology.…”
Section: A Case In Point: the Dutch Vowel Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…helps the learner evaluate alternative hypotheses that could have led to a correct response (Ashby and Maddox, 2011). In the auditory domain, the presence of feedback has been shown to enhance speech category learning in two investigations, but full and minimal feedback conditions could not be compared, as there were only two possible categories (Goudbeek et al, 2008;McCandliss et al, 2002). Full and minimal feedback conditions have been compared in speech category learning with four categories, but generalizability was limited, as the relevant dimensions had not been constrained by the experimenters (Chandrasekaran et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%